The complete chloroplast genome of Lilium Lankongense Franchet (Liliaceae). Issue 1 (2nd January 2019) - Su, Danmei; Li, Juan; Kang, Lu; He, Xingjin; Yu, Yan; Zhou, Songdong
Abstract: The complete chloroplast genome sequence of Lilium lankongense Franchet is presented here. It is 152, 611 bp in length and divides into four distinct regions: small single copy region of 17, 506 bp, large single copy region of 81, 995 bp, and a pair of inverted repeat regions (26, 555 bp). The L. lankongense chloroplast genome annotation predicted a total of 131 genes, which contains 83 protein-coding genes, 38 transfer RNA genes, and 8 ribosomal RNA genes. In the maximum likelihood tree, all kinds of Lilium were clustered into two monophyletic groups.